PANDANGAN TERHADAP KAUM LESBIAN, GAY, BISEXUAL DAN TRANSGENDER (LGBT) DI GEREJA JEMAAT KRISTEN INDONESIA (JKI) OIKOS PELANGI KASIH SEMARANG - Nimas Kasih Krisetiarti; Joko Mahendro; Chlaoudhius Budhianto; Yusup Rogo Yuono; Daryanto (SAGACITY : Journal of Theology and Christian Education, 2023)
Abstract: Speaking of LGBT that is growing in Indonesian society, and not many of God’s children are trapped in the LGBT world. Not few churches have an attitude difference in responding to LGBT’s case. Seeing the growth of LGBT people up to this day has moved the church to serve them through a blossoming, coaching, counselling, and visiting approach. One is the JKI Oikos Church of Semarang Love that has a vision of serving the unserved, especially serving LGBT. In this study refers to understanding how a theological ethical view of LGBT people is. The purpose of this writing is to know how the theological ethics of LGBT people in the JKI Oikos Church view rainbows of love. The data-collection tool done in this study is a descriptive qualitative method described an object and phenomenon as being put in narrative writing, the writing of data and facts in the form of words and written documents both orally and in writing. The result of this study is the JKI Oikos Church of Semarang Love present to be a container for LGBT people whose views are underhanded to society. As for the contribution of this study, LGBT people feel love and apply the love of God shed through the JKI Oikos Rainbow Church of Love. In addition, LGBT people have succeeded in breaking free from their same-sex sinful relationships.